Chronic traumatic encephalopathy in an epilepsy surgery cohort: Clinical and pathologic findings. (6th February 2018) - Jones, Amy L.; Britton, Jeffrey W.; Blessing, Melissa M.; Parisi, Joseph E.; Cascino, Gregory D.
Abstract : Objective: To determine the occurrence of chronic traumatic encephalopathy (CTE) in young adult patients undergoing epilepsy surgery. Methods: Ten patients who underwent epilepsy surgery were randomly selected for this retrospective study. The patients were 18–45 years of age, had preoperative neuropsychological evaluation, and had 1 year postoperative follow-up. Microscopic sections from resections were evaluated for the presence of CTE with standard stains and antibodies to tau (clone AT8). Results: The median age at resection was 32.5 years (range 23–43) and the median duration of seizures was 23.5 years (range 3–28). Eight had a history of head injury. Preoperative neuropsychological testing showed mild to moderate cognitive impairment in 8 patients (80%). Pathologic examination in one patient showed focal sparse tau-immunoreactive lesions along descending rami and cortical gyral depths of the resected frontal lobe. Nine patients had no evidence of CTE. All focal cortical resections showed variable subpial and subcortical gliosis commonly identified in patients with chronic seizure disorders. Conclusions: The present small retrospective observational study suggests that CTE may occur, but appears uncommon, in young adult patients undergoing surgical treatment for drug-resistant focal epilepsy. The significance of these findings requires further investigation to define the relative importance of tau accumulation in younger adult patients with drug-resistant focal epilepsy and cognitive decline.